The association between serum lipid profile and the prostate cancer risk and aggressiveness - Suh, Jungyo; Shin, Teak Jun; You, Dalsan; Jeong, In Gab; Hong, Jun Hyuk; Kim, Choung-Soo; Ahn, Hanjong (Frontiers in Oncology, 2023)
Purpose: This study aims to evaluate the association of serum lipid profile on prostate cancer (PCa) risk and aggressiveness. Methods: Men who underwent prostate biopsy between January 2005 and December 2015 were retrospectively analyzed. The association between lipid profile and the risk, stage, and Gleason grade group (GG) of the PCa were investigated. Sensitivity analysis was conducted using univariate and multivariate quantile analysis for lipide profile on the risk and stage of PCa. Results: Of the 1740 study populations, 720 men (41.4%) were diagnosed as PCa. From multivariate logistic regression analysis, age, prostate specific antigen, triglyceride (odds ratio (OR):1.05, confidence interval (CI):1.03-1.07, p-value<0.001) significantly increased PCa risk, while total cholesterol (OR:0.96, CI:0.92-0.99, p-value=0.011) significantly decreased the PCa risk. The increase of serum triglyceride increased the risk of both of locally advanced (OR:1.03, CI:1.00-1.07, p-value=0.025) and metastatic PCa (OR:1.14, CI:1.04-1.25, p-value=0.004). The increase of serum triglyceride increased the risk of GG2-3 (OR:1.03, CI:1.00-1.06, p-value=0.027) and GG4-5 (OR:1.04, CI:1.01-1.08, p-value=0.027). Univariate quartile analysis founded serum triglyceride increasing risk of locally advanced disease than organ confined disease. (OR: 1.00, 1.25, 2.04, 4.57 for 1st, 2nd, 3rd and 4th quartile, p-value<0.001). Adjusted multivariate quartile analysis confirmed statistically significant increasing PCa risk of triglyceride (OR: 1.00, 1.25, 2.04, 4.57 for 1st, 2nd, 3rd and 4th quartile, p-value<0.001). Conclusions: This study findings suggested increased in triglyceride level increased the risk PCa. Increased in triglyceride level also associated with aggressive presentation of PCa, with higher stage and GG.